Laser field effects on the interaction of charged particles with a degenerate electron gas - Arista, Nestor Ricardo; Galvão, R. O. M.; Miranda, L. C. M. (Comisión Nacional de Energía Atómica; Argentina)
Fil: Arista, Nestor Ricardo. Comisión Nacional de Energía Atómica; Argentina